War and suicide: a comparative analysis of Yukio Mishima and Ernest Hemingway in the context of existentialism and Emile Durkheim’s Study of Suicide - Chowdhury, Sarah Nazia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.